Case Volume Analysis of Neurological Surgery Training Programs in the United States: 2017–2019. (16th November 2020) - Hopkins, Benjamin; Shlobin, Nathan A; Kesavabhotla, Kartik; Smith, Zachary A; Dahdaleh, Nader S
Abstract: INTRODUCTION: Neurological surgery resident applicants seek out certain aspects of training, including case volume. While graduating ACGME summary data is available yearly, it is not program specific and drawing conclusions is difficult. METHODS: ACGME neurosurgical resident national reports from 2017–2019 were downloaded. Averages, standard deviations, and medians were recorded from each of twenty-seven procedural categories. Monte Carlo simulations were performed. Each distribution was run independently one to four times to represent the number of residents in a given program per year. Cases were divided into categories: endovascular, open-vascular, tumor, spine, and pediatrics. RESULTS: Average derived graduating case volumes were 1, 558 cases in 2017, 1, 599 cases in 2018 and 1, 618 cases in 2019. Programs with three residents per year averaged 4, 755 cases per year, with 90th percentile of 5, 401 cases per year. After removing endovascular cases, radiosurgery, and critical care procedures, the average was 3, 794 cases, with 90 th percentile of 4, 197 cases per year. Categorically, the 90 th percentile was 241 for open vascular, 373 for endovascular, 1, 600 for spine, 769 for tumor, and 352 for pediatrics. CONCLUSION: Case volume is an important part of neurosurgical training and a major factor in determining applicant residency program ranking. Through Monte Carlo simulation, the average case volume for programs with three residents per year was determined. Metrics and benchmarking remain an important part of applicant and program growth.